The Success of Contextual Learning from Engineering Teacher Training Students’ Learning Outcomes in Bangladesh - Mohammed Fakir; Rahman Mallik (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2025)
This study aims to evaluate the success of contextual learning implementation in engineering education in Bangladesh, identify the main challenges faced, and provide recommendations to improve the relevance and effectiveness of the method. The background of this study focuses on the importance of implementing learning that connects theory to practice, which can improve student engagement and educational relevance. The method used in this study is a qualitative approach with data analysis obtained through in-depth interviews with lecturers and students and observations of the implementation of contextual learning methods in several engineering educational institutions in Bangladesh. The study’s findings indicate that contextual learning positively impacts students’ understanding of the material and the development of practical skills. However, the main challenges are limited facilities, lack of lecturer training, and misalignment between the curriculum and the project-based approach. The implications of these findings indicate the need for improving educational infrastructure, more intensive training for lecturers, and aligning the curriculum with industry demands to improve the effectiveness of contextual learning. This study recommends strengthening collaboration between educational institutions and the industry sector to provide students with more relevant and applicable learning opportunities.